Pengembangan Bahan Ajar Teks Proseur Berbasis Teknologi untuk Meningkatkan HOTS Siswa Kelas X SMA N 1 Badar - Santriana; Liesna Andriany; Ali (Sintaks: Jurnal Bahasa & Sastra Indonesia, 2022)
This research is aimed to know the feasibility of electronic module-based teaching materials for flip-books in class X SMA. The method used is the 4-D (four D) research method by S. Thiagarajan and the development steps are (1)Define, (2) Design, (3) Development, and (4) Dissemination. The source of data is a questionnaire. The type of data is quantitative descriptive data as the main data collected through an instrument by Likert scale. The respondents are material/language experts, design experts and media experts. The researcher used the validation stage by four expert validators, therefor it could be tested in a limited way, carried out for the dissemination stage. The material expert responses to teaching materials and obtained an average as 83% of all aspects or "very satisfactory" means that the product is feasible and valid to be tested in small and large groups. Meanwhile, the design experts obtained as 98% or "very satisfactory" means that the product is feasible and valid to be tested by small groups and large groups. And from media experts, it was obtained as 93% or "very satisfactory" means that the media was feasible and valid to be tested in small groups and large groups. In the dissemination stage, the authors obtained dissemination scores through 25 respondents. Each respondent gives its value through a questionnaire that the author distributes. The results were collected and analyzed to obtain a good overall score as 85%. It can be concluded that the procedural text module with the media of this flipbook e-module has a good value and feasible to be used as teaching material in carrying out the teaching and learning process for procedural text material.